53.3: Investigation of AlGaN‐based Deep‐UV Micro‐LED as Highly Efficient Excitation Source for Green Perovskite Quantum Dots Display. (26th August 2021) - Feng, Feng; Zhang, Ke; Liu, Yibo; Chan, Ka-Wah; Liu, Zhaojun; Kwok, Hoi-Sing
Abstract : Displays based on inorganic micro light‐emitting diodes (Micro‐LED) are highly anticipated for the next‐generation display technologies. Deep‐UV Micro‐LED as the excitation source for green perovskite quantum dots display with high efficiency is demonstrated in this paper. Deep‐UV Micro‐LEDs were fabricated in different device sizes and lighted‐up on a green perovskite quantum dot film The peak wavelength of Deep‐UV light shows a blue shift with the increasing current density. The light output intensity of a 300 × 200 — pixel Deep‐UV Micro‐LED array with each pixel size of 30×30 µm 2 is shown in the distribution map.